Leadership patterns among schools' administrators in Malaysia - Wan Mahmud, Wan Marfazila; Ab. Jalil, Habibah; Abd Rahman, Fadzilah; Azmi Murad, Masrah Azrifah (IDOSI Publications, 2014)
This paper aims to observe the most dominant leadership patterns within the Malaysian schools administration practitioners. The administrator is a very important person in all matters in schools and one of the matters that seek important role of the administrator is their leadership. This study is to look at the most dominant leadership patterns used by school administrators in the management of their schools based on the results of previous studies that were conducted and also to observe the extent of the leadership pattern used to improve management and achievement in school. Discussion in this paper is based on the analysis of previous journal articles and studies. This paper is written to study the current approaches in leadership patterns used in schools’ management. It will also cover the findings of several studies undertaken in related area. In addition, this article can benefit the school administrators in the aspect of best practices in leadership and management in schools.